2016
DOI: 10.1371/journal.pgen.1006352
|View full text |Cite
|
Sign up to set email alerts
|

Smad2 and Smad3 Regulate Chondrocyte Proliferation and Differentiation in the Growth Plate

Abstract: TGFβs act through canonical and non-canonical pathways, and canonical signals are transduced via Smad2 and Smad3. However, the contribution of canonical vs. non-canonical pathways in cartilage is unknown because the role of Smad2 in chondrogenesis has not been investigated in vivo. Therefore, we analyzed mice in which Smad2 is deleted in cartilage (Smad2CKO), global Smad3-/- mutants, and crosses of these strains. Growth plates at birth from all mutant strains exhibited expanded columnar and hypertrophic zones,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 71 publications
1
42
0
Order By: Relevance
“…A previous study indicated that TGF-β signaling contributed to the development of OA through the activin receptor-like kinase (ALK) 5/SMAD2/SMAD3 pathway or the ALK1/SMAD2/SMAD5 pathway (24). SMAD2 appeared to exhibit a stronger effect on chondrogenesis compared with SMAD3 in vivo (25). In addition, a lower level of SMAD2 protein expression was detected in patients with OA compared with in patients without OA (13).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that TGF-β signaling contributed to the development of OA through the activin receptor-like kinase (ALK) 5/SMAD2/SMAD3 pathway or the ALK1/SMAD2/SMAD5 pathway (24). SMAD2 appeared to exhibit a stronger effect on chondrogenesis compared with SMAD3 in vivo (25). In addition, a lower level of SMAD2 protein expression was detected in patients with OA compared with in patients without OA (13).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have reported that low TGF-β1 concentrations promote the proliferation of muscle, bone (or chondrocytes) and endothelial cells [4,17]. In addition, c-Ski can promote muscle proliferation [18] and participates in endothelial, chondrocyte proliferation [19,20]; c-Ski knockout mice and c-Ski-deficient individuals have defective bone and muscle development [21]. Therefore, these results indicate that proliferation of these cells induced by low TGF-β1 concentrations may also be mediated through the induction of c-Ski.…”
Section: Low Tgf-β1 Concentrations Promote Skin Fibroblast Proliferatmentioning
confidence: 97%
“…Our preliminary data indicate that 3D-Exos might exert its effects through the TGF-β1-dependent Smad2/3 signaling pathway. Several studies have demonstrated that TGF-βs are potent inducer of chondrogenesis (Wang et al 2016;Fig. 2 High-yield exosomes production from hollow-fiber bioreactor.…”
Section: Effect Of Exosomes On the Repair Of Cartilage Defectmentioning
confidence: 99%